Multi-gene phylogeny of Pithomyces with the sexual morph of P. flavus Berk. & Broome - J., Pratibha; Prabhugaonkar, Ashish (Phytotaxa, 2015)
Pithomyces flavus collected from litter of palm, Calamus thwaitesii from Dudhsagar, Goa, India is re-described as sexual morph of Astrosphaeriella vesuvius. Combine molecular phylogenetic analysis of ITS, LSU, SSU and RPB2 is provided to support this new connection and identity of sexual morph.